2019
DOI: 10.1186/s40880-019-0347-y
|View full text |Cite
|
Sign up to set email alerts
|

TES functions as a Mena‐dependent tumor suppressor in gastric cancer carcinogenesis and metastasis

Abstract: BackgroundIn our previous study, we identified a candidate tumor suppressor gene, testin LIM domain protein (TES), in primary gastric cancer (GC). TES contains three LIM domains, which are specific interacting regions for the cell adhesion and cytoskeleton regulatory proteins. Mena is a known cytoskeleton regulator that regulates the assembly of actin filaments and modulates cell adhesion and motility by interacting with Lamellipodin (Lpd). Therefore, we hypothesized that TES plays a role as tumor suppressor i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Downregulation or loss of NDUFA1 expression is a known consistent feature of basal cell carcinoma ( Mamelak et al, 2005 ), while reduced expression of IL13RA1 has been associated with apoptosis and promotion of epithelial to mesenchymal transition (EMT) in pancreatic cancer ( Shi et al, 2022 ). Like OSR1 , TES (testin LIM domain protein) functions as a Mena-dependent tumour suppressor gene in many cancers, including gastric cancer ( Wang et al, 2019 ), with loss of expression associated with cancer progression. However, TES overexpression has been noted in progressive cervical intraepithelial neoplasia ( Popiel et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Downregulation or loss of NDUFA1 expression is a known consistent feature of basal cell carcinoma ( Mamelak et al, 2005 ), while reduced expression of IL13RA1 has been associated with apoptosis and promotion of epithelial to mesenchymal transition (EMT) in pancreatic cancer ( Shi et al, 2022 ). Like OSR1 , TES (testin LIM domain protein) functions as a Mena-dependent tumour suppressor gene in many cancers, including gastric cancer ( Wang et al, 2019 ), with loss of expression associated with cancer progression. However, TES overexpression has been noted in progressive cervical intraepithelial neoplasia ( Popiel et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, we found that knockdown of NAT10 increased the expression levels of miR-9-5p targets, including SH3BP4, NCOR2, LMNA, EPAS1 and TES (NEW Fig. S7 a), which exhibit tumor suppressive properties [ 65 68 ]. Therefore, we believe that some miR-9-5p targets may play a role in regulating tumorigenesis after NAT10 knockdown.…”
Section: Discussionmentioning
confidence: 99%
“…ENO3 is a gene involved in the glycolytic pathway, but seemingly contributes to improved prognosis, with lower levels associated with worse survival in pancreatic cancer [142,143,145]. With respect to TES, while it has been reported to act as a tumor suppressor in other tumor types [146,147], in pancreatic cancer its increased expression seems to be associated with worse survival [143,144].…”
Section: Gene Signatures As Hypoxia Surrogatesmentioning
confidence: 99%